Perioperative/postoperative anxiety and its interventions in gynecological cancers: a comprehensive review of clinical evidence - Chen, Beibei; Chen, Chunyan; Zhao, Xiumin; Xia, Dongyue (Frontiers in Psychiatry, 2024)
Gynecological cancers are prevalent malignancies among females, and surgical intervention is the primary therapeutic approach offering the possibility of a definitive cure. Recent research has highlighted the susceptibility of gynecological cancer patients to experiencing anxiety symptoms during the perioperative and postoperative phases, with this psychological condition being linked to suboptimal recovery following surgery. Nevertheless, certain interventions have shown promise in mitigating perioperative and postoperative anxiety in gynecological cancer patients. In this study, we conducted a comprehensive review to collect the existing evidence on this subject. Through a systematic search across six common databases, we screened and included 28 pertinent studies. The current review emphasizes the elevated occurrence of perioperative and postoperative anxiety among patients with gynecological cancers (i.e., uterine, cervical, ovarian, endometrial, and vulval cancers). Specific nursing interventions (i.e., crisis intervention nursing, multidisciplinary collaborative continuous nursing, psychological nursing, comprehensive psychological nursing, reminiscence therapy involved care, cognitive behavioral stress management, hospital-family integrated continuation nursing, high-quality nursing care, relaxation-focused nursing program, and relaxation/counseling intervention) and psychotropic medications may serve as dependable approaches to mitigate perioperative and postoperative anxiety. This study represents a novel contribution to the literature by providing a characterization of perioperative and postoperative anxiety in the context of gynecological oncology. The findings underscore the significance of addressing perioperative and postoperative anxiety as a critical clinical concern for individuals with gynecological cancers, emphasizing the need for further research to develop effective interventions.